Teaching of Entrepreneurship Development and Management of Small Scale Industries at Regional Engineering College Kurukshetra - Singal, R. K. (Journal of Engineering Education Transformations, 1994)
Realizing the role of small scale industries in creating larger employment opportunities, distribution of ownership, diversification of management and development of rural and backward areas, the Central Government gave major thrust to the development of small scale industries in India.